Background briefs on the Livestock and Fish Program’s work on dairy value chain development in Tanzania - CGIAR Research Program on Livestock and Fish (International Livestock Research Institute, 2013)
Prepared for the Science and Partnership Advisory Committee, Morogoro, Tanzania, 9-11 December 2013